Leadership in a Global World Management Training Requirement Using The Example of The Asian Studies Program at University of Applied Sciences (HTWG) Konstanz - Gabriele Gertrud Thelen (Bright Institute, 2021)
This article demonstrates the need for higher education to systematically cultivate leadership competencies. Values-based leadership is emerging as an attractive international concept, and the related competencies that managers need stem from this. Approaches taken from intercultural communication theory and classical communication psychology show how effectively and clearly value-based actions (speech) can be taught as part of intercultural management training. Experience gained in the interdisciplinary study programs 'Asian Studies' and management (USA) and 'Business and Tourism Germany' (WDT) at HTWG Konstanzi is used as an example to demonstrate teaching formats that can be used to inculcate social competence, and in particular intercultural competence as a competence values-based leadership. This article describes how it is possible to incorporate appropriate teaching formats into management training curricula and also offers observations evaluating the effectiveness of such approaches, including using methods drawn from empirical social research.